Patient preferences, knowledge and beliefs about kidney allocation: qualitative findings from the UK-wide ATTOM programme. Issue 1 (27th January 2017) - Gibbons, Andrea; Cinnirella, Marco; Bayfield, Janet; Wu, Diana; Draper, Heather; Johnson, Rachel J; Tomson, Charles R V; Forsythe, John L R; Metcalfe, Wendy; Fogarty, Damian; Roderick, Paul; Ravanan, Rommel; et al.
Abstract : Objective: To explore how patients who are wait-listed for or who have received a kidney transplant understand the current UK kidney allocation system, and their views on ways to allocate kidneys in the future. Design: Qualitative study using semistructured interviews and thematic analysis based on a pragmatic approach. Participants: 10 deceased-donor kidney transplant recipients, 10 live-donor kidney transplant recipients, 12 participants currently wait-listed for a kidney transplant and 4 participants whose kidney transplant failed. Setting: Semistructured telephone interviews conducted with participants in their own homes across the UK. Results: Three main themes were identified: uncertainty of knowledge of the allocation scheme; evaluation of the system and participant suggestions for future allocation schemes. Most participants identified human leucocyte anitgen matching as a factor in determining kidney allocation, but were often uncertain of the accuracy of their knowledge. In the absence of information that would allow a full assessment, the majority of participants consider that the current system is effective. A minority of participants were concerned about the perceived lack of transparency of the general decision-making processes within the scheme. Most participants felt that people who are younger and those better matched to the donor kidney should be prioritised for kidney allocation, but in contrast to the current scheme, less priority was considered appropriate for longer waiting patients. Some non-medical themes were also discussed, such as whether parents of dependent children should be prioritised for allocation, and whether patients with substance abuse problems be deprioritised. Conclusions: Our participants held differing views about the most important factors for kidney allocation, some of which were in contrast to the current scheme. Patient participation in reviewing future allocation policies will provide insight as to what is considered acceptable to patients and inform healthcare staff of the kinds of information patients would find most useful.